Ethnographic Study of Gender Construction In the Cultural Practices of the Wasilomata Community Central Buton District - Muh. Jamal; Rusman; Budiman; Taat Wulandari (MUWAZAH : jurnal kajian gender, 2024)
This research aims to describe gender construction in Wasilomata community culture related to gender role mapping and access to public power. This research is qualitative with an ethnographic approach. The research location is Wasilomata Village, Southeast Sulawesi, Indonesia. The research informants were customary chiefs, traditional leaders, and village heads, who have knowledge related to the issues under study. Data collection was conducted through observation, interviews, and documentation, with the researcher as the main instrument. Data validity techniques used triangulation, namely cross-checking between interview data, observations, and documents. Data analysis used James P. Spradley's interactive model of ethnographic data analysis. The result of this research is that the socio-cultural system influences the legitimization of male and female power in Wasilomata society. Based on two main foundations for the formation of gender construction in social reality, namely mythical beliefs and religious interpretations in mapping the gender roles of men and women and the basis for the formation of social norms in regulating opportunities for access to public power. Prominent social norms only represent men by prohibiting women from participating at the public level, resulting in gender inequality. The results of this study provide insight into the importance of establishing gender equality in the social structure of society, as well as explaining how inequality between men and women can hinder women from innovating and changing in inclusive social development. This finding can be a valuable asset for efforts to prevent what is relatively a myth in perpetuating gender inequality in various societies.